Cover Image, Volume 84, Issue 10. Issue 10 (October 2016) - Butts, Carter T.; Bierma, Jan C.; Martin, Rachel W.
Abstract : The cover image, by Rachel W. Martin et al., is based on the Article Novel proteases from the genome of the carnivorous plant Drosera capensis: structural prediction and comparative analysis, DOI:10.1002/prot.25095 .